1997
DOI: 10.1210/en.138.7.2735
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Y1-Receptor Stimulation Is Required for Physiological Amplification of Preovulatory Luteinizing Hormone Surges

Abstract: Neuropeptide Y (NPY) has been shown to potentiate the actions of LHRH during the generation of preovulatory LH surges. It is not yet known, however, if activation of a specific subtype of NPY receptors in the anterior pituitary gland is an obligatory event in the stimulation of spontaneous LH surges. A battery of NPY receptor agonists, as well as the specific NPY Y1 receptor antagonist BIBP3226, were used to assess the role of Y1 receptors in the amplification of LH surges. In Exp 1, the potencies of a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…In our hands, central injections of NPY did not inhibit lordosis; however, selective activation of the Y 1 R with LPNY inhibited lordosis. These results are congruent with the finding that Y 1 R mediates NPY actions on LH release Leupen et al, 1997;Li et al, 1999). The present results extend the observation that NPY inhibited lordosis in rats with a very robust estrogen-priming paradigm (100 g of EB) (Clark et al, 1985).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our hands, central injections of NPY did not inhibit lordosis; however, selective activation of the Y 1 R with LPNY inhibited lordosis. These results are congruent with the finding that Y 1 R mediates NPY actions on LH release Leupen et al, 1997;Li et al, 1999). The present results extend the observation that NPY inhibited lordosis in rats with a very robust estrogen-priming paradigm (100 g of EB) (Clark et al, 1985).…”
Section: Discussionsupporting
confidence: 92%
“…The first report of NPY in rats used a supraphysiological dose of estradiol benzoate (EB; 100 g) to induce lordosis (Clark et al, 1985), but a subsequent study repeated their findings with a more physiological relevant dose of EB (5 g), albeit in Syrian hamsters (Corp et al, 2001). Despite these results, the NPY receptor subtype mediating behavioral actions has not been elucidated; the NPY-Y 1 subtype (Y 1 R) is responsible for NPY-induced luteinizing hormone (LH) release Besecke et al, 1994;Leupen et al, 1997). This suggested that Y 1 R might be involved in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…They also noted a negative effect of GnIH on the activity of NPY cells in mice. Of note, it has been shown that activation of the NPY-Y1 receptor is required for the physiological amplification of the spontaneous preovulatory LH surge in rats (Leupen et al 1997). Therefore, GnIH inhibition of NPY cells can also contribute to the inhibitory effect of GnIH on LH surge.…”
Section: Role Of Kp In Regulation Of Reproductionmentioning
confidence: 99%
“…There is considerable evidence, for example, that a preovulatory NPY surge facilitates preovulatory release of gonadotropin-releasing hormone (GnRH) in proestrous rats [1, 2], and to potentiate GnRH-induced luteinizing hormone (LH) secretion from pituitary gonadotropes [3, 4, 5, 6, 7]. These effects appear to be mediated by NPY Y1 receptors expressed in hypothalamic [8, 9]and pituitary [6]cells respectively. Other studies have demonstrated that intracerebroventricular NPY applications can induce changes in basal LH secretion in a steroid dependent manner.…”
Section: Introductionmentioning
confidence: 99%